2012
DOI: 10.1007/s00134-012-2531-2
|View full text |Cite
|
Sign up to set email alerts
|

Adverse cardiac events during catecholamine vasopressor therapy: a prospective observational study

Abstract: Adverse cardiac events occurred in 48.2 % of surgical intensive care unit patients with cardiovascular failure and were related to morbidity and mortality. The extent and duration of catecholamine vasopressor therapy were independently associated with and may contribute to the pathogenesis of adverse cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
159
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(175 citation statements)
references
References 35 publications
(31 reference statements)
3
159
0
6
Order By: Relevance
“…Theoretically, strategies to augment cardiac output and improve oxygen carrying capacity through transfusion would increase oxygen delivery. However, a complicated relationship exists between macrohemodynamics and the microcirculation (61); transfusions may not increase oxygen transport in the manner predicted (62,63); and the use of intravenous fluids (64), vasoactive agents (65), and transfusions (45) has each been associated with adverse consequences. An alternative approach would be to reduce the cerebral metabolic rate of oxygen consumption through targeted temperature management or pharmacologic coma.…”
Section: An Alternative Approach To Oxygenation In Ards: Resetting Thmentioning
confidence: 99%
“…Theoretically, strategies to augment cardiac output and improve oxygen carrying capacity through transfusion would increase oxygen delivery. However, a complicated relationship exists between macrohemodynamics and the microcirculation (61); transfusions may not increase oxygen transport in the manner predicted (62,63); and the use of intravenous fluids (64), vasoactive agents (65), and transfusions (45) has each been associated with adverse consequences. An alternative approach would be to reduce the cerebral metabolic rate of oxygen consumption through targeted temperature management or pharmacologic coma.…”
Section: An Alternative Approach To Oxygenation In Ards: Resetting Thmentioning
confidence: 99%
“…Their therapeutic safety margin is small (2). Dose dependently, adverse cardiac events occur in up to 50% of critically ill patients exposed to catecholamine therapy and are associated with an increase in both morbidity and mortality (3). Aside from unspecific nitric oxide synthase inhibitors [e.g., methylene blue (4)], vasopressin derivatives such as arginine vasopressin or glycylpressin have been clinically evaluated as alternative vasopressor agents to adrenergic agents (5-7).…”
mentioning
confidence: 99%
“…On the basis of previous study results, many intensive care nurses and physicians seem to consider a MAP between 70 and 85 mmHg as the 'comfort zone' . However, vasopressors may have serious adverse effects in critically ill patients with shock [10][11][12], and, therefore, titration of these agents to the lowest necessary dose may be beneficial. In contrast to the clinical trials mentioned above [9,10], retrospective observational studies suggest that MAP levels between 60 and 65 mmHg can best predict survival from septic shock [13,14].…”
mentioning
confidence: 99%
“…The objective to identify a population at specific risk for adverse vasopressor effects is though clinically relevant. Observational studies have suggested that age per se is not an independent risk factor for the occurrence of adverse events during vasopressor therapy [11,12], which emphasizes the need for large-scale RCTs with predefined subgroups and stratification by subgroup before any conclusions can be made. Instead, the intensity of vasopressor therapy and the disease severity may be the most relevant independent risk factors to predict complications.…”
mentioning
confidence: 99%